The Influence of Wŏnhyo’s Understanding of “Shenjie” 神解 on the Chinese Commentaries on the Awakening of Faith in Mahāyāna - Jiyun Kim (Religions, 2023)
This study aims to reveal the influence of Wŏnhyo’s Kisillon so (Wŏnhyoso) on Chinese commentaries on the Awakening of Faith in Mahāyāna (AFM), which is regarded as important in East Asian Buddhism. Previous studies focused only on the influence on Fazang’s Qixinlun shu (Fazangshu), but it should be noted that the Wŏnhyoso also had an effect on the understanding of the AFM in China. First, by comparing the usage of “shenjie” in the Fazangshu and in the Wŏnhyoso, one can identify Wŏnhyoso’s unique interpretation. The Wŏnhyoso defines it as “mystical understanding as the nature of One Mind in the aspect of thusness and the nature of the mind of original enlightenment in the aspect of arising and ceasing”, whereas the Fazangshu defines “shenjie” as “an excellent comprehension”. Next, examining the usage of “shenjie” of the Wŏnhyoso in the later commentaries on the AFM after Fazang, such as the Shilun, the Zanxuanshu, the Puguanji, the Zongmishu, the Bixueji, the Shulue, and the Huiyue, has confirmed the influence of the Wŏnhyoso in Chinese Buddhism. In addition, the relationships between Chinese commentaries on the AFM were also clarified based on the commentaries’ acceptance of “shenjie”.